Production of cellulosic sugars from oil palm empty fruit bunch / Dayang Siti Shamsiah binti Awang Bujang - Awang Bujang, Dayang Siti Shamsiah (2013)
Dilute perchloric acid of up to 12% concentration has been used to digest ground biomass of oil palm empty fruit bunch (OPEFB). The method by-passes the need to chemically pretreat the substrate as the acid perchloric is able to pretreat the lignin and hemicellulose, and subsequently saccharify the cellulosic residues to glucose and other sugars. Two parameters for the dilute acid treatment, namely acid concentration and time of reaction were investigated to optimize the yield of glucose. The optimum conditions for perchloric acid hydrolysis of OPEFB with respect to different concentrations of acid and time at 100˚C were reported. Perchloric acid concentration of 12% and the time of 180 min gave the best yield of 43.7 g of total sugars per 100 g of dry OPEFB. Comparative studies under similar conditions were made for hydrochloric acid, sulphuric acid and perchloric acid. The total sugar yield for sulphuric acid and hydrochloric acid hydrolysis was 27.8 g and 26.7 g of total sugars per 100 g of dry OPEFB, respectively. Excess perchloric acid was neutralised with KOH to yield a precipitate of KClO4, a salt that is easily filtered to yield the sugar-rich hydrolysate. KClO4 may be recycled to perchloric acid. The method represents an option for the production of sugars from lignocellulosic biomass that may be further processed for the production of bioethanol. The final yield of ethanol was 97% based on glucose.